2019
DOI: 10.4236/fns.2019.104028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Coffee on Cisplatin Induced Renal Apoptosis in Adult Male Albino Rats

Abstract: Background: Green coffee as a functional food has an antioxidant effect, which can reduce the cancer incidence, promote weight-loss and improve glucose and lipid metabolism, as well as anti-oxidant and anti-inflammatory activity. Objective: Assessing the effect of green coffee administration on experimental cisplatin induced renal apoptosis in adult male albino rats of local strain. Design: Randomized Block Design was used. Materials and Methods: Forty adult male albino rats of local strain were randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The present study showed that oral GCBE administration caused significant regression of renal histopathologic changes when compared to GIAN model group. In accordance with our results Nour El-Deen et al (2019), reported attenuation of renal apoptosis after administration of GCBE to rats. Such improvement was attributed according to the researchers to the significant proven antioxidant effect of GCBE.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study showed that oral GCBE administration caused significant regression of renal histopathologic changes when compared to GIAN model group. In accordance with our results Nour El-Deen et al (2019), reported attenuation of renal apoptosis after administration of GCBE to rats. Such improvement was attributed according to the researchers to the significant proven antioxidant effect of GCBE.…”
Section: Discussionsupporting
confidence: 93%
“…The proven antioxidant effect of GCBE on other injuries of the kidneys was previously reported. Noureldeen et al demonstrated improvement in renal oxidative stress markers after oral administration of GCBE in rats with cisplation induced renal apoptosis (Nour El-Deen et al, 2019). Also the antioxidant effect of GCBE has been demonstrated in other organs like liver, brain and skin (Nogaim et al, 2020;Pergolizzi et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In line with this finding, Amin et al reported that rats received oral green coffee bean for seven days with the induction of acute renal failure (ARF) showed significantly lower serum creatinine and serum BUN [24]. Comparable studies by Mansour et al reported that green coffee beans had significantly reduced serum creatinine and serum BUN in cisplatin-challenged mice [40]. ese declines in serum creatinine and serum BUN levels in our study may be due to several factors.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, green coffee (100 mg kg −1 ) has a remarkable improvement in the levels of Bax, Casp3, and Bcl-2 compared to the control group. El-Deen et al reported that treatment with green coffee diminished apoptosis and reduced the expression of caspase-3 in the renal tubules 26 .…”
Section: Resultsmentioning
confidence: 99%